2015
DOI: 10.1371/journal.pntd.0003463
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Helminth Infection during Pregnancy on Cognitive and Motor Functions of One-Year-Old Children

Abstract: ObjectiveTo determine the effect of helminth infection during pregnancy on the cognitive and motor functions of one-year-old children.MethodsSix hundred and thirty five singletons born to pregnant women enrolled before 29 weeks of gestation in a trial comparing two intermittent preventive treatments for malaria were assessed for cognitive and motor functions using the Mullen Scales of Early Learning, in the TOVI study, at twelve months of age in the district of Allada in Benin. Stool samples of pregnant women … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
59
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(59 citation statements)
references
References 35 publications
0
59
0
Order By: Relevance
“…A flowchart of the follow-up of pregnant women and children has been published elsewhere. 20 Maternal baseline characteristics were similar between children not assessed and those assessed at age 1 year. 20 Mean maternal age (SD) at first ANC visit was 26.8 (5.6) years.…”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…A flowchart of the follow-up of pregnant women and children has been published elsewhere. 20 Maternal baseline characteristics were similar between children not assessed and those assessed at age 1 year. 20 Mean maternal age (SD) at first ANC visit was 26.8 (5.6) years.…”
Section: Resultsmentioning
confidence: 82%
“…20 Maternal baseline characteristics were similar between children not assessed and those assessed at age 1 year. 20 Mean maternal age (SD) at first ANC visit was 26.8 (5.6) years. The prevalence of malaria was 16.0% at first ANC visit, declined to 3.7% at second ANC visit, and then increased to 10.6% at delivery.…”
Section: Resultsmentioning
confidence: 82%
“…In children with malaria, deficits in fine motor skills were more pronounced in children with cerebral malaria than those with severe malarial anemia while another study found that helminth infection was associated with poor gross motor function (Bangarina et al, 2016; Mireku et al, 2015). …”
Section: General Comprehensive and Specific Neurodevelopment Tests (mentioning
confidence: 99%
“…Numerous studies document the effects of vertically acquired HIV infection in multiple areas of neurodevelopment in school age children including overall cognitive ability, 46,47 memory, perception, 48 motor function, 49, 50 executive function, 51 and language skills. 50, 52 Maternal helminth infection shows effects on children at 1 year of age that may well extend into early to middle childhood, 53 but these effects are so far unstudied. Findings like this highlight the need for longitudinal studies of the effects of maternal or congenital infections on child neurodevelopment across the age span.…”
Section: The Impact Of Inflammation On Neurodevelopment During Early mentioning
confidence: 99%